Insights into base-free OsO4-catalyzed aminohydroxylations employing chiral ligands. Issue 8 (22nd February 2019) - Cardon, Joseph M.; Coombs, James C.; Ess, Daniel H.; Castle, Steven L.
Abstract: Attempts to perform the OsO4 -catalyzed enantioselective base-free aminohydroxylation of β, β-disubstituted enoates are described. Low yields and racemic products were obtained in the presence of standard chiral ligands, suggesting the occurrence of a "Second Cycle" process due to slow hydrolysis of the amino alcohol product from the Os metal center. Support for this hypothesis was provided by the slightly improved enantioselectivity (60:40 er) obtained with an amino alcohol ligand. Based on density functional theory calculations, it is proposed that the lack of significant enantioselectivity is due to a low-energy (3 + 2) oxo/imido cycloaddition transition state without the chiral ligand in the Second Cycle that outcompetes protonolysis in the First Cycle. Graphical abstract: Image 1